Clinical, Virological, Immunological, and Genomic Characterization of Asymptomatic and Symptomatic Cases With SARS-CoV-2 Infection in India - Chatterjee, Sanchari; Datey, Ankita; Sengupta, Soumya; Ghosh, Arup; Jha, Atimukta; Walia, Safal; Singh, Sharad; Suranjika, Sandhya; Bhattacharya, Gargee; Laha, Eshna; Keshry, Supriya Suman; Ray, Amrita; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Purpose: The current global pandemic of Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2 led to the investigation with clinical, biochemical, immunological and genomic characterization from the patients to understand the pathophysiology of viral infection. Methods: Samples were collected from six asymptomatic and six symptomatic SARS-CoV-2 confirmed hospitalized patients in Bhubaneswar, Odisha, India. Clinical details, biochemical parameters, treatment regime were collected from hospital, viral load was determined by RT-PCR, levels of cytokines and circulating antibodies in plasma were assessed by Bioplex and isotyping respectively. In addition, the whole genome sequencing of viral strains and mutational analysis were carried out. Results Analysis of the biochemical parameters highlighted the increased levels of C-Reactive protein (CRP), lactate dehydrogenase (LDH), serum SGPT, serum SGOT and ferritin in symptomatic patients. Symptomatic patients were mostly with one or more comorbidities, especially type 2 diabetes (66.6%). The virological estimation revealed that there was no significant difference in viral load of oropharyngeal (OP) samples between the two groups. Whereas, viral load was higher in plasma and serum samples of symptomatic patients and they develop sufficient amounts of antibodies (IgG, IgM and IgA). The levels of 7 cytokines (IL-6, IL-.1α, IP-10, IL-8, IL-10, IFN-α2, IL-15) were found to be highly elevated in symptomatic patients, while three cytokines (soluble CD40L, GRO and MDC) were remarkably higher in asymptomatic patients. The whole genome sequence analysis revealed that the current isolates were clustered with 19B, 20A and 20B clades, however acquired 11 additional changes in Orf1ab, spike, Orf3a, Orf8 and nucleocapsid proteins. The D614G mutation in spike protein is linked with higher virus replication efficiency and severe SARS-CoV-2 infection as three patients had higher viral load and among them two patients with this mutation passed away. Conclusions This is the first comprehensive study of SARS CoV-2 patients from India. This will contribute to a better understanding of the pathophysiology of SARS-CoV-2 infection and advance in the implementation of effective disease control strategies.